Combination of Acupuncture Points in The Treatment of Hind Leg Paresis with Electroacupuncture Methods in Domestic Cats - Mudhita Zikkrullah Ritonga; Tongku Nizwan Siregar; M Hanafiah; Muttaqien -; Elvina Andali Putri (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2022)
Back leg paresis is muscle weakness that can cause the inability to walk or support the back of the body. A domestic cat, female, black tabby hair colour with a bodyweight of 2.9 kg has weakness in both hind legs so it cannot lift the back of the body properly but there is still a reflex when pressing using tweezers sirurgis on the gluteus muscle tendon. The flexor reflexes on the digits are still present but slightly. From the physical examination, it was concluded that there was a disturbance in the segment IV spinal cord, precisely at L7-S1. Cats also experience problems with defecation, namely the patient's stool is watery inconsistency. The results of the X-Ray examination showed that the segments of the os. lumbar, os. femur, os. tibia, os. fibula, os. metatarsal to digit there are no fractures and also the visceral organs do not experience changes and abnormalities. However, there is a bias picture, namely compression on the 7th segment (S4-L5, L6 and L7). The diagnosis was that the cat had disorders of the spinal cord segments IV (L4-S2) and V, to be precise, from L7 to S2. Electroacupuncture therapy at points BL-18, BL-19, SP-6, ST-36 and LIV-3 was carried out for three weeks, namely twice in the first week and once in the second and third weeks. Oral drug therapy in the form of Neurobion® tablets is taken orally during therapy.